2014
DOI: 10.1080/21642850.2014.908716
|View full text |Cite
|
Sign up to set email alerts
|

Disseminating skills to carers of people with eating disorders: an examination of treatment fidelity in lay and professional carer coaches

Abstract: Family members of people with eating disorders (EDs) have high levels of stress and can use maladaptive methods of coping. We have developed an intervention, using motivational interviewing (MI) strategies that trains lay and professional carer coaches (CCs) to support carers of adolescents with EDs to use more adaptive coping procedures. The aim of this study is to measure treatment integrity in coaches with either academic or lived experience. Eleven coaches were trained and supervised by an expert trainer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The guides had regular supervision. The quality of the sessions was judged for competency in motivational interviewing skills, and the majority were found to be adequate (Macdonald et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The guides had regular supervision. The quality of the sessions was judged for competency in motivational interviewing skills, and the majority were found to be adequate (Macdonald et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Training and the measurement of quality assurance of the coaching has been previously described (Goddard, Raenker, et al, ). The majority of coaches (64%) attained the recommended skill level for motivational interviewing as defined by the standard measure of competence (Macdonald, Hibbs, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…A key advantage of the current design is that we can examine how feasible and acceptable this intervention is in standard treatment settings. Although we have previously used peer support in the context of interventions for carers [ 38 ] and frequently employ such individuals in our inpatient setting to help with teaching and various aspects of the therapeutic environment, we have not yet employed recovered individuals exactly in the capacity as in the Recovery MANTRA intervention. We will thus examine whether this form of task-sharing is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Peer mentors will be assigned study participants only after they have demonstrated sufficient competence with training samples (that is, the training samples will have details of patients who will not be used within the study). Adherence and fidelity to the motivational interviewing model will be monitored by an analysis of a random selection of transcripts (sessions 2 to 5) using the Motivational Interviewing Treatment Integrity rating system, a validated and reliable behavioural coding system used to measure treatment integrity in motivational interviewing [ 38 ]. A simplified version of the Revised Cognitive Therapy Scale [ 39 ] will be adapted specifically for this intervention to address the more goal-driven aspects of the programme.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation